2021
DOI: 10.1093/jas/skab301
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic merit on ewe performance and efficiency parameters

Abstract: The aim of this study was to investigate the impact of ewe genetic merit on ewe performance and efficiency parameters. The study consisted of three genetic merit groups (New Zealand (NZ), High Irish and Low Irish) and ran from 2016 to 2019, inclusive. Each genetic merit group contained 30 purebred Suffolk and 30 purebred Texel ewes, that were selected based on their maternal genetic indexes in their country of origin namely Ireland (€uro-star Replacement index) or New Zealand (New Zealand Maternal worth). Ewe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…However, a greater difference in age at slaughter was observed between animals of high and low genetic merit based on the terminal index (8.34 d) compared to the maternal index (4.45 d), suggesting that the terminal index is selected strongly for lamb postweaning growth potential. The magnitude of the differences between animals of high and low index in the present study was greater than those reported by Fetherstone et al (2021a) for traits including lamb survival and number of lambs born, but very similar in terms of lamb live weights pre and weaning to those reported previously by Márquez et al (2012) at both 5 (+0.3 kg) and 10 (+0.5 kg) weeks of age.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…However, a greater difference in age at slaughter was observed between animals of high and low genetic merit based on the terminal index (8.34 d) compared to the maternal index (4.45 d), suggesting that the terminal index is selected strongly for lamb postweaning growth potential. The magnitude of the differences between animals of high and low index in the present study was greater than those reported by Fetherstone et al (2021a) for traits including lamb survival and number of lambs born, but very similar in terms of lamb live weights pre and weaning to those reported previously by Márquez et al (2012) at both 5 (+0.3 kg) and 10 (+0.5 kg) weeks of age.…”
Section: Discussionsupporting
confidence: 68%
“…The use of selection index theory ( Hazel, 1943 ) to generate a single value of the genetic merit of an animal, is commonly used across farmed species including sheep ( Conington et al, 2004 ; Swan et al, 2007 ; Santos et al, 2015 ), goats ( Ziadi et al, 2021 ), beef ( Twomey et al, 2020 ), and dairy ( Miglior et al, 2005 ). Rates of genetic gain or response to selection are commonly modeled for individual traits for sheep ( Swan et al, 2007 ; Casellas et al, 2015 ; Santos et al, 2017 ), less commonly reported in the literature is the validation of breeding objectives ( Connolly et al, 2016 ; Twomey et al, 2020 ), this is especially true for sheep, where validation studies have tended to focus on specific traits ( Conington et al, 1998 ) or on controlled experiments ( Márquez et al, 2012 ; Fetherstone et al, 2021a , 2021b ). Access to a national database, such as was available in the present study allows, firstly large numbers of animals to be accessed per trait (range 9,197 to 47,169 in the present study) and secondly allows animals to be compared in a commercial environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key performance indicators for each scenario, describing reproductive performance and lambing [4], lamb growth and performance [6], and ewe efficiency and performance [5] were retrieved and inputted to the TLPM, as outlined in Tables 1 and 2. Selection indices for this study were based on those used in the Irish national breeding objectives [1] and hosted by Sheep Ireland (https://www.sheep.ie; accessed on 10 January 2021).…”
Section: Maternal-genetic-merit and Country-of-origin Scenariosmentioning
confidence: 99%
“…The validation of genetic indexes is essential in order to increase farmers’ confidence in breeding programmes and to demonstrate that genetic progress can be achieved through the use of animals of superior genetic merit. Previous research on the impact of maternal genetic merit and country of origin on the productivity of sheep production systems has shown that differences exist in reproduction and lambing performance [ 4 ], lamb growth and performance [ 5 ], and ewe performance and efficiency [ 6 ]. Although differences were often biologically small between the three genetic-merit groups within the previously reported literature, the overall financial impact of the accumulation of these differences at the full farm-system level has not been investigated to date.…”
Section: Introductionmentioning
confidence: 99%